Growth of Educator Competence - Onikoyi, Olawale Abayomi (Jurnal Pendidikan Indonesia Gemilang, 2025)
Educator competence is inextricably linked to educational excellence because the learning process at the heart of education will depend on professional educators. This study aims for researchers to assess the growth of educator competence through the following facets: 1. groundwork, 2. application, and 3. assessment of the ideal for improving primary school educators' competence. This study uses a descriptive qualitative approach with multiple settings and data collection through interviews, recording, and observation. The processes include performance and presumption sketch, with research carried out at Ifako Ijaiye Local Government area in a Primary School and a Primary School under Lagos State Universal Education Board. The outcomes exhibited that: 1. groundwork involves the programs from the Education Board and contribution from inspectors; 2. the application of growth entails the application of growth from the education ministry and in the school; 3. the growth assessment by the education ministry desires to be increased again on the growth occurrence program; the growth substance is focused on real abilities.